2022
DOI: 10.1002/adem.202200945
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydrophilic and Oleophilic Absorption Media from Biotemplated Fungi

Abstract: Fungi are an incredibly diverse biological kingdom with organisms that have a wide range of morphologies, properties, and structures. Previous research has investigated the use of filamentous fungi, which have naturally porous structures created by hyphal filaments, as a means of phytoremediation. This study uses these natural fungal structures to create bioinspired materials that capture both the structure and functional absorption properties of fungi. Three types of filamentous fungi with different hyphal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Bracket fungi, which are typically trimitic and therefore stiffer than other species, have been identified as particularly promising. Beside morphology, hyphal systems impact the mechanical and fluid absorption properties of the mushroom [ 113 , 116 ]. Previous investigations have demonstrated that hyphal structure of mushrooms can be leveraged when choosing between divergent species in the design of PMMs [ 81 , 114 , 117 ].…”
Section: Leveraging Unique Species For Pmmsmentioning
confidence: 99%
“…Bracket fungi, which are typically trimitic and therefore stiffer than other species, have been identified as particularly promising. Beside morphology, hyphal systems impact the mechanical and fluid absorption properties of the mushroom [ 113 , 116 ]. Previous investigations have demonstrated that hyphal structure of mushrooms can be leveraged when choosing between divergent species in the design of PMMs [ 81 , 114 , 117 ].…”
Section: Leveraging Unique Species For Pmmsmentioning
confidence: 99%